And the Oscar goes to ? [computer graphics]. - Perry, T.S (IEEE spectrum)
Discusses the role of computer graphics in the motion picture industry. The work on texture mapping by Catmull, together with the work on fractals by Carpenter, and the work on reflective light by Cook are discussed. This culminated in the RenderMan software. On 3 March 2001, the first Movie-Year-2000 Oscar went to Rob Cook, Loren Carpenter, and Ed Catmull for their work in the field of motion picture rendering as exemplified by RenderMan